Effect of Artisanal Processing on Volatile Compounds and Sensory Characteristics of Traditional Soft-Ripened Cheeses Matured with Selected Lactic Acid Bacteria - José M. Martín Miguélez; Irene Martín; Jurgen Robledo; Sonia Ventanas; Juan J. Córdoba (Foods)
The present research evaluated the effect of selected Lacticaseibacillus casei strains with anti-Listeria monocytogenes properties on the characteristics of traditional soft-ripened cheeses produced in two different seasons. Physicochemical, microbiological, texture, volatile compound, and sensory evaluations were performed on the cheeses after 60 days of ripening. The inoculation with protective cultures of selected LAB did not negatively affect the physicochemical parameters of the cheeses. Thirty-two volatile compounds were identified, including acids, alcohols, ketones, aldehydes, and esters, with differences between productions and inoculated batches. The selected LAB strains improved the sensory profile of the soft-ripened cheeses, decreasing values of texture parameters such as hardness, gumminess, and chewiness related to a softer texture and increasing umami taste and floral and lactic odor attributes. Sensory analysis revealed that consumers perceived differences between inoculated and non-inoculated cheeses, although the overall acceptability was not affected. This study provides valuable information for the artisanal cheese industry, demonstrating that it is possible to use selected protective lactic acid bacteria to assure food safety without compromising traditional flavor and even improving sensorial attributes.